CONTRIBUIÇÕES DA VISÃO SISTÊMICA PARA A COMPREENSÃO DAS DIFICULDADES DE SUPRESSÃO DO DESMATAMENTO NA AMAZÔNIA E CERRADO BRASILEIROS - Azevedo, Roberta Soledade (2011)
This work articulates politics, economics, ecology and epistemology to reflect on the political and environmental problems of protecting the Amazon Rainforest, the largest continuous area of rainforest in the world. The focus of the work is directed to the continuing degradation and deforestation, despite national and international policy efforts since the late twentieth century, such as the Program for Protection of Tropical Forests in Brazil (PPG-7). The theoretical frame of reference is the theory of World-system and Earth-system. The goal is to understand the difficulties of implementing environmental protection policies aimed at the Amazon Rainforest, pointed out in the media, research, assessment reports of plans and governmental. The research is divided into three chapters. In the first chapter we begin by looking at the forest and the issue of vegetation cover reduction in the world, focusing on the period of highest deforestation rate, damage and environmental impact of human history, which is the postwar era. In this initial chapter we present our methodology and capture the lead political, economic, ecological and scientific-technological developments of the key stakeholders, and these political units among themselves and as a whole. Thus, we identify a systemic pattern of political growth and socioeconomic development that drives the development of the projects of the different political units of the system. This pattern of systemic political development in the Amazon region persists even today, which is a huge challenge to the implementation of environmental policies and limited political progress towards its protection. The PPG-7 is presented as an exercise of political cooperation, characterized by the struggle between political forces that began in mid twentieth century. It is a strong emergency precedent in the political and scientific objectives, funding structure, results, and evaluations of this policy of protection of the Brazilian rainforest. We recognize that the environmental problem has political roots, and elaborate on the challenges that Brazil´s insertion in the global economy represent, as federal projects, formulated to support and balance the system expansion, provide the rise of political units in the modern system. In the second chapter we focus on the connections and interdependence in the modern world. We present the conceptual idea of world-system and system-land, as well as theoretical andoperational efforts of a more comprehensive and dynamic reality. Its scientific basis is distinct from the mechanical model and the fragmented understanding of the real political, economical, ecological and scientific causes of the Amazon deforestation in the postwar era. As a conclusion, we affirm the necessity of incorporating an integrated and systemic view in political studies, which means recognizing the interdependence between the Earth system and the World-system, the importance of the development of instruments and mechanisms of political decision making, and the strategic planning of space exploration in Brazil, more aligned with the challenges and opportunities ahead.